The existence of global strong and weak solutions for the Novikov equation - Lai, Shaoyong; Li, Nan; Wu, Yong Hong (Academic Press, 2013)
The well-posedness of the global strong and weak solutions for the Novikov equation is investigated. Provided that initial value u0 ∈ Hs(s > 3/2) and satisfying a sign condition, the existence and uniqueness of global strong solutions for the equation are shown to be valid in Sobolev space. The estimates in Hq(R) space with 0≤q≤1/2, which are derived from the equation itself, are developed to prove the existence and uniqueness of the global weak solutions.